2015
DOI: 10.1093/ejcts/ezu525
|View full text |Cite
|
Sign up to set email alerts
|

V-composite grafting using the right internal thoracic artery grafts anastomosed to aorto-coronary bypass grafts

Abstract: V-composite grafting using the RITA and the A-C bypass graft provides excellent clinical outcomes with satisfactory early and 1-year patency rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Atherosclerotic stenosis of the subclavian artery or brachiocephalic trunk is sometimes associated with coronary artery disease [ 3 ]. Many patients with stenosis of the subclavian artery or brachiocephalic trunk are asymptomatic; however, the stenosis can cause stroke during CABG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Atherosclerotic stenosis of the subclavian artery or brachiocephalic trunk is sometimes associated with coronary artery disease [ 3 ]. Many patients with stenosis of the subclavian artery or brachiocephalic trunk are asymptomatic; however, the stenosis can cause stroke during CABG.…”
Section: Discussionmentioning
confidence: 99%
“…An 8-mm polytetrafluoroethylene graft was anastomosed to the right subclavian artery, and then the proximal end of this graft was anastomosed to the aorta with a side-biting clamp. Off-pump CABG was then performed using a method described previously [ 3 ]. The left internal thoracic artery and the free right internal thoracic artery were anastomosed to the left anterior descending artery and the left circumflex artery, respectively.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a Y‐composite graft can be made with the conventional HEARTSTRING technique, a V‐composite graft is preferrable because Y‐composite grafts of the free IMA from the SVG may lead to a steal phenomenon and/or a slit phenomenon. Nishigawa et al reported that a V‐composite graft suppresses the influence of the inflow conduit and improves the patency of the composite RIMA . Making a V‐composite graft is reasonable, and one HEARTSTRING system can easily make a V‐composite graft.…”
Section: Commentmentioning
confidence: 99%
“…Nishigawa et al reported that a V-composite graft suppresses the influence of the inflow conduit and improves the patency of the composite RIMA. 2 Making a V-composite graft is reasonable, and one HEARTSTRING system can easily make a V-composite graft. This technique can also be applied to making V-composite grafts with multiple vein grafts, with or without a RIMA graft.…”
Section: Commentmentioning
confidence: 99%